A review of the spider genus Porrhomma (Araneae, Linyphiidae) - Růžička, Vlastimil (Zootaxa, 2018)
The spider genus Porrhomma has been revised; it now includes 24 species. Two new species are described: Porrhomma altaica new species from the Altai Mountains, and Porrhomma nekolai new species from eastern Asia and North America. Bathyphantes charpentieri Lebert, 1877 was removed from synonymy with Porrhomma microphthalmum (O. Pickard-Cambridge, 1871). The following new synonymies are proposed: Bathyphantes charpentieri Lebert, 1877 is a junior synonym of Porrhomma convexum (Westring, 1851) new synonymy; Porrhomma gertschi Hackman, 1954 is a junior synonym of Porrhomma terrestre (Emerton, 1882) new synonymy; Porrhomma myops Simon, 1884 is a junior synonym of Porrhomma rosenhaueri (L. Koch, 1872) new synonymy; Porrhomma ocella Chamberlin & Ivie, 1943 is a junior synonym of Porrhomma convexum (Westring, 1851) new synonymy; Porrhomma omissum Miller, 1971 is a junior synonym of Porrhomma egeria Simon, 1884 new synonymy; Porrhomma pallidum affinis Miller & Kratochvíl, 1940 is a junior synonym of Porrhomma pallidum Jackson, 1913 new synonymy; Porrhomma sodonta (Chamberlin, 1949) is a junior synonym of Porrhomma convexum (Westring, 1851) new synonymy. The synonymy of Porrhomma macrochelis (Emerton, 1917) with Macrargus multesimus (O. Pickard-Cambridge, 1875) is supported. Porrhomma subterraneum Simon, 1884 is considered a nomen dubium, because it was described according to a juvenile specimen. To date, Porrhomma indecorum Simon, 1910 and Porrhomma marphaense Wunderlich, 1983 are only known from findings of females; they are considered to be species inquirenda, and their names are declared nomina dubia. Keys are provided for males and females. Vulvae are drawn in dorsal, ventral and caudal views to understand their spatial structure.